Fishery management problems in Malaysia : the need for a fresh approach. - Mohamed, Mohd. Ibrahim (1989)
The merits and problems in fishery management are well known and documented. In a multispecies and multigear fishery like Malaysia. fishery management problems are further compounded by the large number of species and multiple gear operated. A brief discussion on the present management system and its constrants are presented. This has resulted in conflicts and overexploitation of resources both biologically and economically. When scientist and fishery managers develop a fishery management plan. often no attempts are made to include fishermen's views and participation. Thus the practical implementation of the plan is not given the full considerations. This paper examines some of the problems of fishery management in Malaysia and proposes a fresh look at the planning and implementation of the fishery management plan. The intimate relationship between the fishermen. fish and the sea should be used more effectively to ensure a more practical management system that will meet with the aspirations of the managers and the managed.